Carbon monoxide shift catalyst as well as preparation method and application thereof
By introducing structural additives and modification additives into the copper-based carbon monoxide transformation catalyst, the composition and structure of the catalyst are optimized, and the problems of poor heat resistance and low selectivity of the catalyst at high temperatures are solved, thereby achieving efficient high-CO content raw material gas transformation reaction.
Patent Information
- Application Number
- CN202311409016.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The existing copper-based carbon monoxide conversion catalysts have poor heat resistance and low selectivity at high temperatures, so they cannot effectively treat raw material gas with high CO content.
Introduce structural additives and modification additives to optimize the composition and structure of the catalyst and improve its heat resistance and selectivity. Structural additives include Cr, Ca, Ce and Zr, and modification additives include Li, Na, K and La.
It significantly improves the heat resistance and selectivity of the catalyst, and is suitable for raw material gas transformation reactions with high CO content at high temperatures, reduces the generation of side reactions, and improves the market promotion value of the product.
Smart Images

Figure BDA0004517518560000131 
Figure BDA0004517518560000132 
Figure BDA0004517518560000141
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a carbon monoxide conversion catalyst and a preparation method and application thereof. Background Art
[0002] Carbon monoxide conversion (abbreviated as conversion) is an important part of modern coal chemical projects. Through the conversion reaction, CO in the raw gas is converted into H2, and the hydrogen-carbon ratio in the raw gas is adjusted to meet the requirements of downstream devices. The conversion reaction is a reversible exothermic reaction. Traditional conversion technology generally uses multiple adiabatic conversion reactors in series to achieve the required conversion depth. With the continuous development of coal gasification technology, dry coal powder quenching process gasification technology has been widely used. The raw coal gas produced by this type of gasification technology has the "double high" characteristics of high water content and high CO content. If it directly enters the conversion furnace for reaction, the catalyst bed temperature will be as high as 500°C or above, which seriously affects the service life of the catalyst and the safe operation of the system. The traditional adiabatic conversion technology generally uses a high water-gas ratio or a low water-gas ratio process to prevent the catalyst bed from overheating.
[0003] However, neither the high water-gas ratio process nor the low water-gas ratio process can fundamentally solve the problem of using catalysts at high temperatures. In recent years, isothermal shift technology has received attention from many scientific research institutions and enterprises, and has made breakthrough developments, fundamentally solving the problem of overheating of the catalyst bed in the "double high" crude gas shift reaction. Catalysts are the key to achieving advanced processes.
[0004] The catalysts currently used in conjunction with isothermal reactors have two problems. On the one hand, the performance in the high-temperature zone is relatively low. When the temperature is higher than 320°C, the CO conversion rate shows a significant downward trend. On the other hand, there are many side reactions. The content of alcohols in the liquid phase (aqueous phase) product of the reaction increases significantly with the increase of reaction temperature, which increases the subsequent separation cost.
[0005] The existing copper-based shift catalysts are mainly composed of copper, zinc, and aluminum, and are usually only suitable for shift reactions at low temperatures (180-220°C) and low CO content (<5% by volume). For shift reactions at higher reaction temperatures and higher CO content, the catalysts show the disadvantages of poor heat resistance and low selectivity. Some researchers are also trying to add other additives to the system to improve the performance of the catalyst, especially to enhance its heat resistance and selectivity.
[0006] In existing research, the heat resistance of the catalyst has been improved to a certain extent, but the selectivity of the catalyst is still not high, which affects the market promotion and use of the catalyst products. It is urgent to develop a transformation catalyst with strong heat resistance and selectivity to meet the requirements of the transformation reaction. Summary of the invention
[0007] The object of the present invention is to provide a copper-based carbon monoxide isothermal shift catalyst having strong heat resistance and high selectivity and a preparation method thereof.
[0008] The present invention introduces a structural additive to change the composition of the catalyst, optimize the catalyst structure, and improve the heat resistance of the catalyst.
[0009] The present invention introduces a modification aid to effectively inhibit the occurrence of side reactions and improve the selectivity of the catalyst.
[0010] According to a first aspect of the present invention, a carbon monoxide conversion catalyst is provided, the catalyst components comprising Cu, Zn, Al and an additive; the additive comprises a structural additive and a modifying additive, wherein the structural additive comprises one or more of Cr, Ca, Ce and Zr, and the modifying additive comprises one or more of Li, Na, K and La.
[0011] According to a second aspect of the present invention, a method for preparing the catalyst of the present invention is provided, the method comprising:
[0012] S1. Adding a mixed solution of copper nitrate, zinc nitrate and nitrate of a structural additive into a prepared alkaline precipitant for neutralization and aging;
[0013] S2, the material obtained in step S1 is subjected to sedimentation washing, and alumina powder is added to pulp;
[0014] S3, after pulping, the material is subjected to solid-liquid separation and drying;
[0015] S4, adding the modified auxiliary agent source solution to the dried filter cake, grinding, granulating and drying;
[0016] S5. After drying, the particles are calcined and formed to obtain a catalyst.
[0017] According to the third aspect of the present invention, there is provided an application of the catalyst of the present invention in an isothermal transformation reaction of a raw gas containing a high CO volume content; preferably, the application in an isothermal transformation reaction of calcium carbide tail gas and electric furnace tail gas.
[0018] The present invention introduces a structural additive for the first time, changes the composition of the catalyst, optimizes the catalyst structure, and improves the heat resistance of the catalyst; and introduces a modification additive for the first time, effectively inhibits the occurrence of side reactions, and improves the selectivity of the catalyst. DETAILED DESCRIPTION
[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0020] The present invention provides a carbon monoxide conversion catalyst, the catalyst components include Cu, Zn, Al and an additive; the additive includes a structural additive and a modified additive, wherein the structural additive includes one or more of Cr, Ca, Ce and Zr, and the modified additive includes one or more of Li, Na, K and La. The present invention introduces a structural additive for the first time, changes the composition of the catalyst, optimizes the catalyst structure, and improves the heat resistance of the catalyst; introduces a modified additive for the first time, effectively inhibits the occurrence of side reactions, and improves the selectivity of the catalyst.
[0021] In the present invention, any catalyst having the aforementioned catalyst components can achieve the purpose of the present invention, and the specific composition thereof can be selected in a wide range, which is exemplified below, but is not limited to the scope of the present invention.
[0022] The various components of the catalyst of the present invention are preferably present in the catalyst in the form of oxides.
[0023] According to a preferred embodiment of the present invention, based on the total weight of the catalyst, the CuO content in the catalyst composition is 20-50wt%, the ZnO content is 30-50wt%, the Al2O3 content is 5-25wt%, the structural auxiliary oxide content is 2-20wt%, and the modification auxiliary oxide content is 0.1-10wt%; the above catalyst composition can ensure the heat resistance and high selectivity of the catalyst.
[0024] According to a preferred embodiment of the present invention, based on the total weight of the catalyst, preferably, the CuO content is 30-36wt%, the ZnO content is 32-40wt%, the Al2O3 content is 9-20wt%, the structural auxiliary oxide content is 5-15wt%, and the modification auxiliary oxide content is 1-4wt%. The above catalyst composition can ensure the heat resistance and high selectivity of the catalyst.
[0025] According to a preferred embodiment of the present invention, preferably, the molar ratio of copper to zinc is 0.8-1.05. The above catalyst composition can ensure the heat resistance and high selectivity of the catalyst.
[0026] The catalyst having the above-mentioned composition of the present invention can achieve the purpose of the present invention, and there is no special requirement for its preparation method. The following exemplifies an embodiment of the catalyst of the present invention, but does not limit the scope of the present invention. According to the present invention, the preparation method of the catalyst includes:
[0027] S1. Adding a mixed solution of copper nitrate, zinc nitrate and nitrate of a structural additive into a prepared alkaline precipitant for neutralization and aging;
[0028] S2, the material obtained in step S1 is subjected to sedimentation washing, and alumina powder is added to pulp;
[0029] S3, after pulping, the material is subjected to solid-liquid separation and drying;
[0030] S4, adding the modified auxiliary agent source solution to the dried filter cake, grinding, granulating and drying;
[0031] S5. After drying, the particles are calcined and formed to obtain a catalyst.
[0032] The purpose of the present invention can be achieved by preparing the catalyst according to the aforementioned steps. There are no special requirements for the operating conditions of each step. The following is an exemplary description, but the scope of the present invention is not limited thereto.
[0033] The solid-liquid separation is performed, for example, by suction filtration.
[0034] There is no special requirement for the number of sedimentation times, for example, it is generally 3 times, and there is no special requirement for the time of adding alumina powder to pulp, for example, it is generally 0.3-0.5h
[0035] According to a preferred embodiment of the present invention, preferably, the mixed solution in step S1 is added for 18-25 minutes.
[0036] In the present invention, there is no special requirement for the concentration of each substance in the mixed solution, for example, the concentration of copper nitrate is 50-400 g / L, the concentration of zinc nitrate is 50-400 g / L and the concentration of nitrate of the structural additive is 5-200 g / L.
[0037] According to a preferred embodiment of the present invention, in the mixed solution, the concentration of copper nitrate is 100-200 g / L, the concentration of zinc nitrate is 100-200 g / L and the concentration of nitrate of the structural additive is 15-80 g / L.
[0038] In the present invention, there is no special requirement for the alkaline precipitant. For example, the concentration of the alkaline precipitant solution is 0.5-2 mol / L. The alkaline precipitant is selected from sodium carbonate, for example, but the scope of the present invention is not limited thereby.
[0039] According to a preferred embodiment of the present invention, preferably, the step of adding the mixed solution in step S1 comprises: the feeding speed is 75-80 ml / min in the first 10 min, and the feeding speed is 65-70 ml / min thereafter.
[0040] According to a preferred embodiment of the present invention, preferably, the neutralization temperature in step S1 is 79-81° C. According to a preferred embodiment of the present invention, the neutralization endpoint pH value in step S1 is 7.2-7.3.
[0041] According to a preferred embodiment of the present invention, the aging temperature after neutralization in step S1 is 80-85° C. According to a preferred embodiment of the present invention, the aging time after neutralization in step S1 is 0.3-0.5 h.
[0042] In the present invention, the range of the types of the modification aid source is relatively wide, and commonly used raw materials can be used in the present invention. According to the present invention, the modification aid source in step S4 is preferably nitrate and / or hydroxide.
[0043] According to a preferred embodiment of the present invention, preferably, the calcination temperature of the material in step S5 is 450-500°C.
[0044] According to a preferred embodiment of the present invention, preferably, the material calcination time in step S5 is 2.0-4.0 hours.
[0045] According to a preferred embodiment of the present invention, preferably, the weight loss of the material in step S5 is 8-10%.
[0046] The catalyst of the present invention is particularly suitable for use in the isothermal shift reaction of raw gas containing a high CO volume content; preferably, it is suitable for use in the isothermal shift reaction of calcium carbide tail gas and electric furnace tail gas.
[0047] In the present invention, the raw gas with a high CO volume content refers to a raw gas with a CO content higher than 30 volume %.
[0048] The catalyst of the present invention has good high temperature resistance, can be applied to isothermal conversion reactions at a temperature of 190-500° C., and has good selectivity.
[0049] According to a preferred embodiment of the present invention, preferably, the operating conditions of the isothermal shift reaction include: inlet temperature of 190-260°C, reaction pressure of 1.2-3.0 MPa, steam / feed gas (dry gas) of 0.45-0.55, and space velocity of 800-2000 h -1 .
[0050] In the present invention, the catalyst needs to be reduced before use. There is no special requirement for the reduction conditions. Commonly used reduction conditions can be used in the present invention. In the embodiment, the activation conditions are: reducing atmosphere N2 / H2 mixed gas (H2 accounts for 10%, and the rest is N2); reduction pressure: normal pressure-0.2Mpa; reduction space velocity 800h -1 The temperature was slowly raised to 250°C and held for 2.0 h (heating rate 1.5°C / 3 min) as an exemplary illustration, but the present invention is not limited thereto.
[0051] The present invention is further described in detail below in conjunction with specific implementation modes.
[0052] In the present invention, the catalyst composition is obtained by analyzing the product using a chemical method.
[0053] Example 1
[0054] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 80°C for use.
[0055] (1) Add 210 g of copper nitrate (trihydrate), 258 g of zinc nitrate (pentahydrate) and 48 g of zirconium nitrate (pentahydrate) to deionized water to prepare 1.5 L of a mixed solution at 80°C.
[0056] (2) The mixed solution was added to the solution in reactor A at 70 ml / min for the first 10 min and 65 ml / min for the last 12 min. The end point pH value was 7.2. The mixture was stirred and aged at 85°C for 0.4 h.
[0057] (3) After three sedimentation washes, the material was added with 33 g of alumina powder and slurried for 0.3 h.
[0058] (4) After pulping, the material is filtered and dried, and then 4 g of potassium hydroxide is added to grind the material, granulate and dry.
[0059] (5) The dried particles were calcined at 500° C. for 2.0 h, and the material lost 9% of its weight after burning. The catalyst sample Y1 was obtained by tableting.
[0060] Example 2
[0061] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 81°C for use.
[0062] (1) Add 200 g of copper nitrate (trihydrate), 264 g of zinc nitrate (pentahydrate) and 84 g of chromium nitrate (nonahydrate) to deionized water to prepare 1.5 L of a mixed solution at 81°C.
[0063] (2) The mixed solution was added to the solution in reactor A at 75 ml / min for the first 10 min and then at 70 ml / min. The end point pH value was 7.3. The mixture was stirred and aged at 85°C for 0.3 h.
[0064] (3) After three sedimentation washes, the material was added with 33 g of alumina powder and slurried for 0.4 h.
[0065] (4) After the pulping, the material is filtered and dried, and then 3.5 g of sodium hydroxide is added to grind the material, granulate and dry.
[0066] (5) The dried particles were calcined at 480° C. for 3.0 h, and the material lost 8.5% of its weight during burning. The catalyst sample Y2 was obtained by tableting.
[0067] Example 3
[0068] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 81°C for use.
[0069] (1) Add 220 g of copper nitrate (trihydrate), 250 g of zinc nitrate (pentahydrate) and 41 g of cerium nitrate (hexahydrate) to deionized water to prepare a 1.5 L mixed solution at 80°C.
[0070] (2) The mixed solution was added to the solution in reactor A at 70 ml / min for the first 10 min and then at 65 ml / min. The end point pH value was 7.2. The mixture was stirred and aged at 85°C for 0.4 h.
[0071] (3) After three sedimentation washes, 33.5 g of alumina powder was added and slurried for 0.3 h.
[0072] (4) After the pulping, the material is filtered and dried, and then 3.5 g of potassium nitrate is added to grind the material, granulate and dry.
[0073] (5) The dried particles were calcined at 450° C. for 4.0 h, and the material lost 9% of its weight during burning. The catalyst sample Y3 was obtained by tableting.
[0074] Example 4
[0075] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 81°C for use.
[0076] (1) Add 225 g of copper nitrate (trihydrate), 240 g of zinc nitrate (pentahydrate) and 45 g of zirconium nitrate (pentahydrate) to deionized water to prepare a 1.5 L mixed solution at 80°C.
[0077] (2) The mixed solution was added to the solution in reactor A at 70 ml / min for the first 10 min and then at 60 ml / min. The end point pH value was 7.3. The mixture was stirred and aged at 85°C for 0.4 h.
[0078] (3) After three sedimentation washes, the material was added with 32 g of alumina powder and slurried for 0.3 h.
[0079] (4) After the pulping, the material is filtered and dried, and then 4.5 g of potassium hydroxide is added to grind the material, granulate and dry.
[0080] (5) The dried particles were calcined at 500° C. for 3.0 h, and the material lost 8% weight by burning. The catalyst sample Y4 was obtained by tableting.
[0081] Example 5
[0082] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 81°C for use.
[0083] (1) Add 210 g of copper nitrate (trihydrate), 258 g of zinc nitrate (pentahydrate), 35 g of zirconium nitrate (pentahydrate) and 24 g of chromium nitrate (nonahydrate) to deionized water to prepare 1.5 L of a mixed solution at 81°C.
[0084] (2) The mixed solution was added to the solution in reactor A at 72 ml / min for the first 10 min and then at 65 ml / min. The end point pH value was 7.3. The mixture was stirred and aged at 85°C for 0.4 h.
[0085] (3) After three sedimentation washes, the material was added with 35 g of alumina powder and slurried for 0.4 h.
[0086] (4) After the pulping, the material is filtered and dried, and then 4.5 g of potassium hydroxide is added to grind the material, granulate and dry.
[0087] (5) The dried particles were calcined at 500°C for 3.0 h, and the material lost 10% of its weight during burning. The catalyst sample Y5 was obtained by tableting.
[0088] Example 6
[0089] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 81°C for use.
[0090] (1) Add 210 g of copper nitrate (trihydrate), 258 g of zinc nitrate (pentahydrate), 35 g of zirconium nitrate (pentahydrate) and 24 g of chromium nitrate (nonahydrate) to deionized water to prepare 1.5 L of a mixed solution at 81°C.
[0091] (2) The mixed solution was added to the solution in reactor A at 75 ml / min for the first 10 min and then at 65 ml / min. The end point pH value was 7.3. The mixture was stirred and aged at 82°C for 0.5 h.
[0092] (3) After three sedimentation washes, the material was added with 33 g of alumina powder and slurried for 0.4 h.
[0093] (4) After the pulping, the material is filtered and dried, and then 3 g of lanthanum nitrate is added, ground, granulated and dried.
[0094] (5) The dried particles were calcined at 480° C. for 3.5 h, and the material lost 9% of its weight during burning. The catalyst sample Y6 was obtained by tableting.
[0095] Example 7
[0096] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 81°C for use.
[0097] (1) Add 210 g of copper nitrate (trihydrate), 258 g of zinc nitrate (pentahydrate), and 45 g of zirconium nitrate (pentahydrate) to deionized water to prepare a 1.5 L mixed solution at 81°C.
[0098] (2) The mixed solution was added to the solution in reactor A at 75 ml / min for the first 10 min and then at 65 ml / min. The end point pH value was 7.3. The mixture was stirred and aged at 83°C for 0.5 h.
[0099] (3) After three sedimentation washes, the material was added with 34 g of alumina powder and slurried for 0.4 h.
[0100] (4) After the pulping, the material is filtered and dried, and then 2g potassium hydroxide and 1g sodium hydroxide are added to grind the material, granulate and dry.
[0101] (5) The dried particles were calcined at 480° C. for 3.5 h, and the material lost 8.5% of its weight during calcination. The catalyst sample Y7 was obtained by tableting.
[0102] Example 8
[0103] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 81°C for use.
[0104] (1) Add 210 g of copper nitrate (trihydrate), 258 g of zinc nitrate (pentahydrate), and 65 g of calcium nitrate (tetrahydrate) to deionized water to prepare a 1.5 L mixed solution at 81°C.
[0105] (2) The mixed solution was added to the solution in reactor A at 75 ml / min for the first 10 min and then at 65 ml / min. The end point pH value was 7.3. The mixture was stirred and aged at 85°C for 0.5 h.
[0106] (3) After three sedimentation washes, the material was added with 34 g of alumina powder and slurried for 0.4 h.
[0107] (4) After pulping, the material is filtered and dried, and then 3 g of potassium hydroxide is added to grind the material, granulate and dry.
[0108] (5) The dried particles were calcined at 480° C. for 3.5 h, and the material lost 9% of its weight during burning. The catalyst sample Y8 was obtained by tableting.
[0109] Example 9
[0110] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 81°C for use.
[0111] (1) Add 235 g of copper nitrate (trihydrate), 220 g of zinc nitrate (pentahydrate), and 45 g of zirconium nitrate (pentahydrate) to deionized water to prepare a 1.5 L mixed solution at 81°C.
[0112] (2) The mixed solution was added to the solution in reactor A at 70 ml / min for the first 10 min and then at 65 ml / min. The end point pH value was 7.3. The mixture was stirred and aged at 85°C for 0.3 h.
[0113] (3) After three sedimentation washes, the material was added with 35 g of alumina powder and slurried for 0.4 h.
[0114] (4) After pulping, the material is filtered and dried, and then 3 g of potassium hydroxide is added to grind the material, granulate and dry.
[0115] (5) The dried particles were calcined at 500°C for 3 h, and the material lost 9.5% of its weight during calcination. The catalyst sample Y9 was obtained by tableting.
[0116] Comparative Example 1
[0117] The preparation was carried out according to Example 1, except that no structural auxiliary agent was added.
[0118] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 80°C for use.
[0119] (1) Add 210 g of copper nitrate (trihydrate) and 258 g of zinc nitrate (pentahydrate) to deionized water to prepare 1.5 L of a mixed solution at 80°C.
[0120] (2) The mixed solution was added to the solution in reactor A at 70 ml / min for the first 10 min and then at 65 ml / min. The end point pH value was 7.2. The mixture was stirred and aged at 85°C for 0.4 h.
[0121] (3) After three sedimentation washes, the material was added with 33 g of alumina powder and slurried for 0.3 h.
[0122] (4) After pulping, the material is filtered and dried, and then 4 g of potassium hydroxide is added to grind the material, granulate and dry.
[0123] (5) The dried particles were calcined at 500° C. for 2.0 h, and the material lost 9% of its weight after burning. The catalyst sample D1 was obtained by tableting.
[0124] Comparative Example 2
[0125] The preparation was carried out in accordance with Example 1, except that no modifying agent was added.
[0126] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 80°C for use.
[0127] (1) Add 210 g of copper nitrate (trihydrate), 258 g of zinc nitrate (pentahydrate) and 48 g of zirconium nitrate (pentahydrate) to deionized water to prepare 1.5 L of a mixed solution at 80°C.
[0128] (2) The mixed solution was added to the solution in reactor A at 70 ml / min for the first 10 min and then at 65 ml / min. The end point pH value was 7.2. The mixture was stirred and aged at 85°C for 0.4 h.
[0129] (3) After three sedimentation washes, the material was added with 33 g of alumina powder and slurried for 0.3 h.
[0130] (4) After pulping, the material is filtered and dried, and then deionized water is added to grind the material, granulate and dry.
[0131] (5) The dried particles were calcined at 500° C. for 2.0 h, and the material lost 9% of its weight after burning. The catalyst sample D2 was obtained by tableting.
[0132] Comparative Example 3
[0133] The preparation was carried out in accordance with Example 1, except that no structural additive and modifying additive were added.
[0134] Prepare a sodium carbonate solution with a concentration of 1.0 mol / L, take 5.5 L and put it into a reactor A equipped with a stirring paddle and water bath heating, and heat it to 80°C for use.
[0135] (1) Add 210 g of copper nitrate (trihydrate) and 258 g of zinc nitrate (pentahydrate) to deionized water to prepare 1.5 L of a mixed solution at 80°C.
[0136] (2) The mixed solution was added to the solution in reactor A at 70 ml / min for the first 10 min and then at 65 ml / min. The end point pH value was 7.2. The mixture was stirred and aged at 85°C for 0.4 h.
[0137] (3) After three sedimentation washes, the material was added with 33 g of alumina powder and slurried for 0.3 h.
[0138] (4) After pulping, the material is filtered and dried, and then deionized water is added to grind the material, granulate and dry it.
[0139] (5) The dried particles were calcined at 500° C. for 2.0 h, and the material lost 9% of its weight after burning. The catalyst sample D3 was obtained by tableting.
[0140] Comparative Example 4
[0141] Prepared according to Example 1 of patent CN 101786000 A.
[0142] Catalyst performance test conditions:
[0143] Isothermal fixed bed reactor, catalyst loading 40 ml (original particle size), raw gas composition (v / v%): CO30%, CO29%, H2 40%, N2 20%, also contains about 1% impurity gas, steam-gas ratio (water vapor / dry gas molar ratio) 0.45, reaction pressure 2.0 MPa, space velocity 1500 h -1 , inlet temperature 200-260℃. The catalyst needs to be reduced before use, activation conditions: reducing atmosphere N2 / H2 mixed gas (H2 accounts for 10%, the rest is N2); reduction pressure: normal pressure-0.2Mpa; reduction space velocity 800h -1 ; The temperature was slowly raised to 250°C and held for 2.0 h (heating rate 1.5°C / 3 min).
[0144] CO conversion rate calculation formula:
[0145]
[0146] Where: Φ1: CO volume fraction in the inlet gas (raw gas), %
[0147] Φ2: CO volume fraction in the outlet gas (product gas);
[0148] The alcohol content test was calculated by liquid chromatography analysis.
[0149] Table 1 Comparison data of embodiments and comparative examples
[0150] catalyst Inlet temperature℃ Hot spot temperature ℃ CO content% CO conversion rate % Alcohol content ppm Y1 250 280 30 94.5 2000 Y2 250 280 30 94.3 1950 Y3 250 280 30 94.5 1990 Y4 250 277 30 94.0 2100 Y5 250 278 30 94.1 2150 Y6 250 278 30 93.9 2090 Y7 250 277 30 93.8 2100 Y8 250 277 30 94.0 2200 Y9 250 279 30 93.7 2170 D1 250 275 30 89.5 2150 D2 250 275 30 93.0 3000 D3 250 275 30 92.1 3100 D4 250 274 30 92.2 3150
[0151] Table 2 Comparison data of embodiments and comparative examples
[0152]
[0153]
[0154] From the data in Tables 1 and 2, it can be seen that the catalyst prepared by the present invention has excellent performance, the addition of structural additives can significantly improve the heat resistance of the catalyst, and is suitable for the requirements of the high-content CO feed gas shift reaction, and the addition of modified additives can inhibit side reactions and effectively reduce the amount of alcohols generated in the liquid phase product of the shift reaction. At the same time, it can be seen that the performance of the catalyst prepared by the present invention is better than that of the catalyst prepared by the process introduced in other technologies.
[0155] The present invention and its implementation methods are described schematically above, and the description is not restrictive. Therefore, if a person skilled in the art is inspired by it and creatively designs similar solutions and embodiments to the technical solution without departing from the purpose of the invention, they should all fall within the scope of protection of the present invention.
[0156] Although the present invention has been disclosed as above in terms of preferred embodiments, they are not intended to limit the present invention. Anyone skilled in the art can make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection defined by the claims of this application.
Claims
1. A carbon monoxide conversion catalyst, characterized in that The catalyst components include Cu, Zn, Al and an auxiliary agent; the auxiliary agent includes a structural auxiliary agent and a modified auxiliary agent, wherein the structural auxiliary agent includes one or more of Cr, Ca, Ce and Zr, and the modified auxiliary agent includes one or more of Li, Na, K and La.
2. The catalyst according to claim 1, wherein Based on the total weight of the catalyst, the catalyst composition comprises 20-50wt% CuO, 30-50wt% ZnO, 5-25wt% Al2O3, 2-20wt% structural additive oxide, and 0.1-10wt% modified additive oxide; Preferably, the CuO content is 30-36wt%, the ZnO content is 32-40wt%, the Al2O3 content is 9-20wt%, the structural additive oxide content is 5-15wt%, and the modification additive oxide content is 1-4wt%; Preferably, the copper to zinc molar ratio is 0.8-1.
05.
3. The method for preparing the catalyst according to any one of claims 1 to 2, characterized in that: The method includes: S1. Adding a mixed solution of copper nitrate, zinc nitrate and nitrate of a structural additive into a prepared alkaline precipitant solution for neutralization and aging; S2, the material obtained in step S1 is subjected to sedimentation washing, and alumina powder is added to pulp; S3, after pulping, the material is subjected to solid-liquid separation and drying; S4, adding the modified auxiliary agent source solution to the dried filter cake, grinding, granulating and drying; S5. After drying, the particles are calcined and formed to obtain a catalyst.
4. The preparation method according to claim 3, wherein: The mixed solution in step S1 is added for 18-25 min; and / or In the mixed solution, the concentration of copper nitrate is 50-400 g / L, the concentration of zinc nitrate is 50-400 g / L and the concentration of nitrate of the structural additive is 5-200 g / L; Preferably, In the mixed solution, the concentration of copper nitrate is 100-200 g / L, the concentration of zinc nitrate is 100-200 g / L and the concentration of nitrate of the structural additive is 15-80 g / L; The concentration of the alkaline precipitant solution is 0.5-2 mol / L, and the alkaline precipitant is selected from sodium carbonate.
5. The preparation method according to claim 3 or 4, wherein The step of adding the mixed solution in step S1 includes: the adding speed is 70-75 ml / min in the first 10 min, and the adding speed is 65-70 ml / min thereafter.
6. The preparation method according to any one of claims 3 to 5, wherein: Step S1: Neutralization temperature 79-81°C; and / or The neutralization end point pH value in step S1 is 7.2-7.3; and / or Step S1: after neutralization, the aging temperature is 80-85°C; and / or The aging time after neutralization in step S1 is 0.3-0.5h.
7. The preparation method according to any one of claims 3 to 6, wherein: In step S4, the source of the modification aid is nitrate and / or hydroxide.
8. A method according to any one of claims 3 to 7, wherein The material calcination temperature of step S5 is 450-500° C.; and / or the material calcination time of step S5 is 2.0-4.0 h.
9. A method according to any one of claims 3 to 8, wherein In step S5, the material is calcined to lose weight by 8-10%.
10. Use of the catalyst according to any one of claims 1 or 2 in the isothermal shift reaction of a raw gas containing a high volume content of CO; preferably in the isothermal shift reaction of calcium carbide tail gas and electric furnace tail gas; Preferably, the operating conditions of the isothermal shift reaction include: The inlet temperature is 190-260℃, the reaction pressure is 1.2-3.0MPa, the steam / raw gas (dry gas) is 0.45-0.55, and the space velocity is 800-2000h -1 .
Citation Information
Patent Citations
CO shift catalyst and preparation method thereof
CN101786000A
CO-containing raw gas conversion and heat recovery method
CN111268645A
Copper-based low-temperature shift catalyst and preparation method thereof
CN112206763A
Carbon monoxide shift catalyst and preparation method thereof
CN113083312A
Copper-based microchannel low-temperature shift catalyst, preparation method thereof and microchannel low-temperature shift reaction method
CN113457688A